Geometric optimisation of volumetric solar receivers: a study of polygonal cavity configurations - Abdullah Ayed Alrwili; Qing Qin; Khalifa Aliyu Ibrahim; Peter King; Thomas Delaney; Ahmed Ali Aldubayyan; Yousef Lafi A Alshammari; Zhenhua Luo (Results in Engineering)
Volumetric solar receivers integrated with reticulated porous ceramics (RPCs) are a key component in high-temperature concentrated solar power (CSP) systems, enabling efficient radiative absorption and convective heat transfer. While prior studies have largely focused on material properties and operating conditions, the influence of cavity geometry on thermal performance remains underexplored. This study presents a systematic computational investigation of four polygonal cavity configurations: hexagonal, heptagonal, octagonal, and nonagonal, using high-fidelity CFD simulations in ANSYS Fluent coupled with the Monte Carlo radiation model. All designs were evaluated under consistent geometric constraints and two solar heat flux inputs (4.1 kW and 4.9 kW), with varying air mass flow rates. The nonagonal receiver achieved the highest thermal efficiencies of 75 % and 73 % at the respective flux levels, outperforming conventional designs. This improvement is attributed to its compact internal structure and increased edge count, which enhance surface energy density and fluid–wall interaction. The findings demonstrate that geometric optimisation, particularly through polygonal cavity design, offers a viable pathway to enhance the thermal performance of volumetric receivers. This work provides new design insights for next-generation CSP applications requiring compact, high-efficiency thermal energy conversion.